Sub-Band Full-Duplex for 5G New Radio: Challenges, Solutions and Performance - Giupponi, Lorenza; Fodor, Gabor; Ambede, Abhishek; Hui, Dennis; Goransson, Bo; Barros Da Silva, Jose Mairton (Conference record - Asilomar Conference on Signals, Systems, & Computers, 2023)
Recently, multiple works in the literature have presented encouraging results on the feasibility of in-band full-duplex (IBFD) communications in point-to-point and single cell arrangements, where the IBFD capability is provided by the base station. However, in multi-cell networks, in addition to high self-interference, full-duplex operations also face the severe problems of base station-to-base station cross-link interference (CLI), inter-sector CLI, user equipment-to-user equipment CLI, and inter-operator interference. Due to these difficulties, the research and engineering communities have recently proposed to adopt sub-band full-duplex (SBFD), as an intermediary step towards IBFD in the evolution of 5G New Radio systems. With SBFD, cellular base stations may operate the downlink and uplink on different non-overlapping frequency sub-bands within a time division duplexing carrier, which helps reduce self-interference and CLI due to the frequency isolation between the uplink and downlink sub-bands. In this paper, we focus on Frequency Range 1 operation, investigate the novel SBFD concept, and compare it to traditional time division duplexing, using realistic assumptions on multi-cell deployments, adjacent channel leakage, CLI and self-interference cancellation techniques. Our results indicate that SBFD operation may primarily be a candidate for low power deployments, with complexity and feasibility challenges in scenarios using high base station transmission power, sectorization, and in the presence of multiple operators.